Practical project control manager handbook : from back-office manager to trusted project strategist - Averous, Jeremie (Singapore : Fourth Revolution Publishing, ., 2016)
In this book, you are taken through a pragmatic practitioner's journey of how to establish and run Project Control to give reliable management information enabling timely management intervention. The Project Control Manager Handbook is both informative and easy to read. It would sit comfortably in any Project Delivery professional's bookcase." - Jonathan Crone, Director of the Programme Management Office, High Speed 2 Ltd. Practical Project Control Manager Handbook: From Back-Office Manager to Trusted Project Strategist Project Control Managers when they exist in Projects are still too often focused on data-crunching and reporting. They do not deliver the potential immense value they could provide in terms of analysis, forecasting and strategic support. The ambition of this must-have handbook is to change this situation. It may well be the first ever Project Control Manager Handbook published. It originated in the trenches of actual Project execution: it is not a heavy and detailed bible, but rather a practical reference for Project practitioners to understand the principles and traps of of Project Control Management over the entire lifecycle of Large or Complex Projects. In addition, the handbook details best practice roadmaps for Project start-up, monitoring and close-out. This handbook complements our trilogy of Advanced Handbooks on Project Control functions (Cost Control, Schedule and Project Risk).
Includes index.
oif 22/01/2020
Loans
Keywords: Project management